2020
DOI: 10.1016/j.bbr.2020.112549
|View full text |Cite
|
Sign up to set email alerts
|

First step of odorant detection in the olfactory epithelium and olfactory preferences differ according to the microbiota profile in mice

Abstract: We have previously provided the first evidence that the microbiota modulates the physiology of the olfactory epithelium using germfree mice. The extent to which changes to the olfactory system depend on the microbiota is still unknown. In the present work, we explored if different microbiota would differentially impact olfaction. We therefore studied the olfactory function of three groups of mice of the same genetic background, whose parents had been conventionalized before mating with microbiota from three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It draws us to things or away from things based on how we perceive odors. This includes our food as shown in Table 3 [115][116][117][118]. Characterization of microbiota among three distinct groups of mice: C3H/HeN, Swiss, and BALB/cByJ.…”
Section: Smellmentioning
confidence: 99%
See 1 more Smart Citation
“…It draws us to things or away from things based on how we perceive odors. This includes our food as shown in Table 3 [115][116][117][118]. Characterization of microbiota among three distinct groups of mice: C3H/HeN, Swiss, and BALB/cByJ.…”
Section: Smellmentioning
confidence: 99%
“…It draws us to things or away from things based on how we perceive odors. This includes our food as shown in Table 3 [ 115 , 116 , 117 , 118 ].…”
Section: Who Behavioral Modification #1: Eat a Healthy Diet (In Spite Of The Microbiota-driven Sense Control)mentioning
confidence: 99%
“…It draws us to things or away from things based on how we perceive odors. This includes our food as shown in Table 3 [115][116][117][118]. As with taste there are thresholds of odor detection and there is the nature of the scent itself.…”
Section: Smellmentioning
confidence: 99%
“…Nardon et al [115] found evidence that microbiota can affect the first step in odor detection at the level of the olfactory epithelium. Studies in three different groups of mice examined the effects of microbiota on nasal epithelium and odor detection and preferences in three different groups of mice using physiological, biochemical, behavioral, and microbiological analyses.…”
Section: Sensementioning
confidence: 99%
“…The metabolism of aroma compounds in the oral cavity originates from the presence of xenobiotic-metabolizing enzymes in saliva and the oral mucosa. , In addition to host enzymes, the oral cavity is colonized by microorganisms, which have their own metabolism and enzymes. A body of evidence suggests that oral microbiota metabolism takes part in in-mouth aroma metabolism through the involvement of specific microbial enzymes. For instance, glycosidases and carbon–sulfur lyases (C–S lyases) have been suggested to play a role in the metabolism of two classes of aroma precursors, namely glycoside conjugates and cysteine conjugates, respectively . These aroma precursors are not perceived as odorants mainly due to the presence of a hydrophilic group, reducing their volatility and binding to the receptors (e.g., the sugar group or cysteine group).…”
Section: Introductionmentioning
confidence: 99%